The Habituation Method of Dhuha Prayer in Standardizing Prayer Recitations at Khoiru Ummah Islamic Junior High School, Malang - Gusti Bayu Mandastana; Muhammad Annas Firdaus; Dina Mardiana (International Journal of Islamic Educational Research, 2026)
This research is motivated by the gap between the standard prayer readings of Khoiru Ummah Islamic Junior High School Malang and the diverse practices of students due to differences in background. The absence of a specific time allocation for talaqqi becomes a challenge in standardization efforts. The purpose of this study is to describe the implementation steps of the guided habituation method through the Jahr technique (loud reading) in congregational Dhuha Prayer as a pedagogical solution. This study uses a qualitative research approach with a case study design. Data were collected through non-participant observation, in-depth interviews with the Principal and Islamic Education Teachers, and Focus Group Discussions (FGD) with students, and document analysis. The results show that the implementation of this method follows the habit loop flow (trigger, routine, reward) from a behavioristic perspective. The Jahr technique functions as an effective auditory stimulus (talaqqi) in helping students memorize standard readings, supported by the fiqh-pedagogical justification of Jahr li at-ta'lim. Despite its effectiveness, challenges were identified in the consistency of student responses (passive) and the lack of systematic post-prayer reinforcement. It was concluded that the guided habituation method through the Dhuha Prayer Session is a practical pedagogical model that can be implemented to standardize practical worship in schools.